Psychometric Characteristics of a Jordanian Version ‎of the‏ ‏Autism Spectrum Rating Scale (ASRS-3) for ‎Ages 6 to 18 Years - Abu Awwad, Ferial; Abd-Al-Latif, Najah (Jordan Journal of Educational Sciences, 2023)
This study aimed to derive psychometric characteristics of a Jordanian version of the Autism Spectrum Rating Scale (ASRS) for ages 6–18..To achieve the aim of the study, a Jordanian version of the autism spectrum disorder scale was prepared and applied to a random sample consisting of 370 individuals diagnosed with autism spectrum disorder, in the age group 6–18 years. The findings showed that the diagnostic and treatment scale items on the Jordanian version of the autism spectrum disorder scale had the proper discriminatory indicators. The findings also demonstrated that the scale had construct validity by using differences between typically developing and autistic children, factorial analysis, and content validity in terms of logical validity. The results also showed the reliability index of the Jordanian version of the scales using the test-retest and internal consistency methods, with all values above 0.80 for Cronbach's alpha